A preliminary investigation of the well-being of visually impaired ex-service personnel in the United Kingdom. (May 2022) - Godier-McBard, Lauren R; Castle, Claire L; Heinze, Nikki; Hussain, Syeda F; Borowski, Shelby; Vogt, Dawne S; Gomes, Renata SM; Fossey, Matt
Research has shown that visual impairment may impact daily functioning, health, and well-being negatively for adults of all ages. Ex-service personnel ('veterans') too may be at risk of poor health and well-being outcomes associated with post-military life, and this may be exacerbated by the presence of visual impairment. Despite this, research considering the experience of blind veterans has been limited and has not yet assessed well-being for these individuals across a broad spectrum of life domains. Rather, it has highlighted poor mental health and psychological well-being in working-age visually impaired veterans. However, the experiences of older visually impaired veterans (who make up the majority of visually impaired veterans in the United Kingdom) have been poorly represented in the literature. This pilot study aimed to provide a preliminary assessment of holistic well-being in an adult sample of 97 UK blind veterans, predominantly composed of older age veterans (majority over 80 years). Cross-sectional well-being data were collected using a validated measure of well-being (the Well-Being Inventory [WBI]). Results suggest that members of Blind Veterans UK are functioning well and are satisfied across four life domains (vocation, finances, health, and social relationships). Lower health satisfaction was identified, particularly in blind veterans with comorbid mental health conditions. Results are discussed in relation to the older age of the sample, the limitations of face-to-face survey administration, and the applicability of the WBI finance domain in this age cohort. Recommendations are made for future research in this population.